Implementation of Talaqqi, Simai, Wahdah, Talqin and Kitabah Methods in Memorizing the Quran: How Do Teachers Guide Students - Anwar, Fuady; Taqiyuddin, Muhammad Fikri; Wijaya, Krisna; Azmi, Muhamad Cholik Yuswara; Izharman, Izharman (Khalifa Journal of Islamic Education, 2022)
Becoming a memorizer (hafizd) of the Quran is not an easy matter, because it requires sincere intentions, sincerity, determination, hard work, strong motivation and of course using the right method. Regarding the method of memorizing the Quran, there are actually many methods that can be chosen and implemented when someone memorizes the Quran. This study aims to identify whether the method of memorizing the Quran used by teachers in guiding students in memorizing the Quran at the Quran memorizing institution Fastabiqul Khairat Indonesia. This study uses a qualitative method with a case study approach. Sources of data were taken through in-depth interviews with five informants (teachers and students), to support the interview data the author also conducted observations and directly interacted with informants in various Quranic activities at the research location. All interview results were then analyzed thematically using NVivo12 qualitative analysis software. The research findings found five methods used by teachers in guiding students in memorizing the Quran. The five methods are: i) Talaqqi Method, ii) Simai, iii) Wahdah, iv) Kitabah, and v) Talqin. In addition, the research findings also prove that the selection of the right method has succeeded in delivering successful students to become a memorizer (hafizd) of the Quran.